2010
DOI: 10.1021/ma9025515
|View full text |Cite
|
Sign up to set email alerts
|

Interchain Hydrogen-Bonding-Induced Association of Poly(acrylic acid)-graft-poly(ethylene oxide) in Water

Abstract: Poly(acrylic acid)-graft-poly(ethylene oxide) (PAA-g-PEO) in aqueous solutions shows one fast and one slow relaxation mode in dynamic light scattering (DLS), but the mixture of PAA and PEO (PAA/PEO) in aqueous solution only has a single fast mode. The effects of pH, polymer concentration, and salt concentration on these two modes have been investigated using laser light scattering (LLS), viscometry, and rheological measurements. Our results showed that the hydrogen bonding between carboxylic group and ether ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 53 publications
5
68
0
3
Order By: Relevance
“…Hydrogen bonds could also possibly form between PEO and PAA chains at low pH, although this was observed for high-molar-mass polymers in solution and is not easily predicted for surface-immobilized low-molar-mass polymers as found here. 46 The scheme thus aims at better describing the interface and its further interactions with proteins by showing the more probable conformations, although it is not possible to predict these conformations fully and, in particular, the PEO−PAA interactions. On the basis of the expected mixed-brush structure, the choice of adequate pH and I conditions to maximize adsorption and desorption of different proteins is facilitated without examining the whole pH−I domain experimentally.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen bonds could also possibly form between PEO and PAA chains at low pH, although this was observed for high-molar-mass polymers in solution and is not easily predicted for surface-immobilized low-molar-mass polymers as found here. 46 The scheme thus aims at better describing the interface and its further interactions with proteins by showing the more probable conformations, although it is not possible to predict these conformations fully and, in particular, the PEO−PAA interactions. On the basis of the expected mixed-brush structure, the choice of adequate pH and I conditions to maximize adsorption and desorption of different proteins is facilitated without examining the whole pH−I domain experimentally.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the results from light scattering showed that the hydrogen bonding between carboxylic group and ether oxygen led to the formation of large complexes among PAA-g-PEO chains. 24 The above fact indicated that the large complex indeed formed through the hydrogen-bonding interaction between the grafted side-chain PEO and the PAA backbone. In addition, compared to the dielectric spectra of PAA solution, the number of relaxations for the PAA-g-PEO-7% solution is one more than that for PAA solution, which shows that the new relaxation for the PAA-g-PEO-7% solution should be associated with the grafted side-chain PEO which formed the large complex.…”
Section: Low-frequency Relaxationmentioning
confidence: 95%
“…According to the literature, 24 each PAA molecule grafted around 9.4 PEO molecules in PAA-g-PEO-7% molecules. In other words, the concentration of the complex formed by the side-chain PEO is greater than the PAA-g-PEO-7% concentration.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Although hydrogen bonding is strong at low pH, it may stabilize aggregated structures in a cooperative manner in neutral or even weak basic conditions. This has been shown in [21] where the PAA-g-PEO copolymer showed aggregation at high pH contrary to the mixture of linear homopolymer PAA and PEO. There, it was claimed that the entropic cost for aggregation is lower in the case of preajoined PEO segments in a PAA backbone.…”
Section: Kinetics Of Peo-b-pnipam-b-paa Assemblymentioning
confidence: 69%